Effect of Nano Cr2O3 in HTPB/AP/Al Based Composite Propellant Formulations - Kshirsagar, Dhirendra; Kurva, Ramesh; Dhabbe, Kashinath; Jawale, Lalita; Singh, Sudhir; Khire, Vrushali; Maurya, Mehilal (Defence Science Journal, 2016)
Different compositions have been prepared by incorporating nano sized chromium oxide from 0.25 % to 1 % in HTPB/AP/Al based composite propellant formulation having 86% of solid loading and studied its effect on viscosity build-up, thermal, mechanical and ballistic properties. The findings reveal that on increasing the percentage of nano Cr2O3 in the composition, there is an increase in end of mix viscosity, elastic modulus and tensile strength while elongation decreases accordingly. The data on thermal properties envisage the reduction in thermal decomposition temperature of ammonium perchlorate as well as formulations based on HTPB/AP/Al. The data on ballistic properties reveal that there is an enhancement in burning rate from 6.11 mm/s to 7.88 mm/s at 6.86 MPa, however, marginal increase in pressure exponent (‘n’ values) from 0.35 to 0.53 with 1 wt % of nano Cr2O3 was observed in comparison to reference composition without chromium oxide.